Management of Teachers Competence Development In Improving Learning Quality in Jeneponto Regency (A Case Study of Madrasah Tsanawiyah) - Abdul Rahman; Basri Modding; Achmad Gani; Nurlaelah Nurlaelah (JED (Jurnal Etika Demokrasi), 2022)
This research aims to analyze planning for competency development of madrasah tsanawiyah teachers; (2) to analyze strategy for developing the competence of madrasah tsanawiyah teachers; (3) to analyze the competence of madrasah tsanawiyah teachers; (4) analyze the barriers and challenges in developing the competence of teachers. The study used primary data through interviews and questionnaires as many as 63 informants as samples based on sample criteria, with details of 3 principal informants, 30 teachers and 30 students as informants. The results of this study indicate that: (1)The planning for developing the competence of madrasah tsanawiyah teachers  is a plan that has been structured, programmed and becomes a system in every madrasah, in carrying out the planning for developing the competence of teachers ; (2)The head of madrasah tsanawiyah as a leader in each institution implements various strategies for developing competence of madrasah tsanawiyah teachers  by motivating and involving teachers  to participate in various scientific activities such as activating MGMP, KKG, seminars, training and workshops; (3)The competence of madrasah tsanawiyah teachers  is in accordance with National Education standards; (4) SWOT analysis used to determine the strengths, weaknesses, opportunities and threats in developing the competence of madrasah tsanawiyah teachers  in order to improve the quality of their professionalism individually nor together. This means that the development of teachers Competence is competent in accordance with national education standards in Jeneponto Regency.